Breastfeeding Knowledge among a Sample of Women attending Maternal and Pediatric Hospital of Soran City - kareem jamal hamad; Hiwa Abdulrahman Awlla (Polytechnic Journal)
Breastfeeding is the ideal method suited for the physiological and psychological needs of an infant and the most vital intervention for reducing infant mortality and ensuring optimal growth and development of a child. Human breast milk is considered the healthiest form of milk for children and contains essential nutrients, vitamins, and minerals during the first six months. The purpose of this study was to find out about breastfeeding knowledge and its relationship with women’s socio-demographic characteristics.